2017
DOI: 10.18632/oncotarget.20893
|View full text |Cite
|
Sign up to set email alerts
|

PARK14 PLA2G6 mutants are defective in preventing rotenone-induced mitochondrial dysfunction, ROS generation and activation of mitochondrial apoptotic pathway

Abstract: Mutations in the gene encoding Ca2+-independent phospholipase A2 group 6 (PLA2G6) cause the recessive familial type 14 of Parkinson’s disease (PARK14). Mitochondrial dysfunction is involved in the pathogenesis of Parkinson’s disease (PD). PLA2G6 is believed to be required for maintaining mitochondrial function. In the present study, rotenone-induced cellular model of PD was used to investigate possible molecular pathogenic mechanism of PARK14 mutant PLA2G6-induced PD. Overexpression of wild-type (WT) PLA2G6 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…Several animal models have demonstrated that expression of iPLA2β prevents the loss of mitochondrial membrane potential and attenuates the cytochrome c release, the decrease of ROS and mitochondrial lipid peroxidation in response to stress-induced apoptosis, protecting mitochondria. The apoptotic cascade, ROS and lipid peroxides are enough to originate a neuroinflammation response, which may potentiate PLAN pathogenesis [ 106 , 119 , 120 , 121 ].…”
Section: Nbia Types Related To Lipid Metabolism and Membrane Remodmentioning
confidence: 99%
“…Several animal models have demonstrated that expression of iPLA2β prevents the loss of mitochondrial membrane potential and attenuates the cytochrome c release, the decrease of ROS and mitochondrial lipid peroxidation in response to stress-induced apoptosis, protecting mitochondria. The apoptotic cascade, ROS and lipid peroxides are enough to originate a neuroinflammation response, which may potentiate PLAN pathogenesis [ 106 , 119 , 120 , 121 ].…”
Section: Nbia Types Related To Lipid Metabolism and Membrane Remodmentioning
confidence: 99%
“…Azoramide reduces the increase in ROS and ameliorates the decline in mitochondrial membrane potential in PLA2G6 D331Y/D331Y midbrain DA neurons Oxidative stress causes the release of cytochrome c from mitochondria, which activates the apoptotic pathway [21][22][23][24][25] . Intracellular ROS in DA neurons was measured with the fluorescent probe CellROX® Green Reagent.…”
Section: Azoramide Attenuates Loss Of Pla2g6 D331y/d331y Ipscderived mentioning
confidence: 99%
“…The phospholipase A2 activity of PLA2G6 was measured using a modified commercial kit that was originally designed for cPLA2 (Cayman Chemicals), as described previously (19). Briefly, the total protein was extracted and incubated in a modified calcium-free buffer (4 mM EGTA, 160 mM HEPES, pH 7.4, 300 mM NaCl, 8 mM Triton X-100, 60% glycerol, and 2 mg/mL BSA) with arachidonoyl thiophosphatidylcholine (ARA-PC) and the synthetic substrate of phospholipase for 2 h at room temperature.…”
Section: Phospholipase Activitymentioning
confidence: 99%